ANALISIS RENCANA DAN REALISASI PROGRAM KEGIATAN CORPORATE SOCIAL RESPONSIBILITY PT PLN (PERSERO) - Nadim, Sy; Matsum, Junaidi H.; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is entitled "Analysis of Plans and Realization of PT PLN (Persero) Main Unit Corporate Social Responsibility Activities in West Kalimantan". The problem in this research is how to plan and realize the Corporate Social Responsibility activity program of PT PLN (Persero) Main Unit in West Kalimantan. The method used is descriptive method. The form of research is descriptive qualitative. The data collection technique in this study was direct communication with the data collection tool using interview guidelines, direct observation using the data collection tool observation sheets, and documentary studies using data collection tools in the form of data archives. The results of the research are (1) planning of CSR activity programs has been well planned, starting from preparing targets and objectives for implementing CSR activities, preparing measuring instruments for the performance of CSR activities, identifying the level of readiness for implementing CSR activities, determining areas of operation for implementing CSR activities, involve the parties concerned, and prepare CSR programs; (2) CSR programs that have been planned are more focused on sustainable programs; (3) The realized CSR program runs well.